Ethnicities in conflict: an ethnocritical approach to Quince Duncan’s “Duel Between Friends” (1970) and Dolores Joseph Montout’s “Adina” (1984) - Marín Maroto, Isaac (2026)
Afro-Costa Rican literature has stood out for its valuable contributions to national literature. Among these contributions, it is worth highlighting linguistic, ethnic, and historical diversity, as well as criticism of a society that has long assumed itself to be white and Spanish-speaking. Theoretical and methodological approaches such as ethnocriticism are useful for analyzing literary representations of the diversity of ethnicities that are part of Costa Rican culture, especially given the conflicting dynamics they raise. In this context, few studies have so far articulated Costa Rican texts written in different languages, which becomes possible and necessary through the analysis of a corpus of Afro-Costa Rican literature. Therefore, this article seeks to analyze the self-representations and hetero-representations of ethnicities in the Costa Rican short stories “Duelo entre amigos” (1970) by Quince Duncan and “Adina” (1984) by Dolores Joseph Montout from an ethnocritical perspective. Based on this study, it is evident that the stories shape decolonial and anti-racist perspectives, problematizing Costa Rican national ideals through plurality and diversity, as well as taking a stand against injustice and inequality.